Mind and method of the legal academic - "Smits, Jan M." (Cheltenham, 2012)
Jan Smits assesses the recent turn away from doctrinal research towards a more empirical and theoretical way of legal investigation and offers a fresh perspective on what it is that legal academics should deal with and how they should do it. The book also considers the consequences which follow for the organization of the legal discipline by universities and uses this context to discuss the key questions of the internationalization of law schools, quality assessments, legal education and the research culture.
Keywords: Legal science